QuEChERS combined with ultra-high performance liquid chromatography-tandem mass spectrometry to determine acrylamide in Xinjiang Naan products - XU Man; SONG Shaolong; HU Jun; SHI Haiyun; LIU Jian (Shipin yu jixie, 2024)
ObjectiveThis study aimed to establish a rapid and accurate analytical method for the determination of acrylamide in Xinjiang characteristic Naan products.MethodsThe methodology involved adding the internal standard 13C3-acrylamide isotope to the samples, followed by the sequential addition of 9 mL of water, 10 mL of acetonitrile, 6 mL of n-hexane, 6 g of anhydrous magnesium sulfate, and 1.5 g of sodium acetate salting agent. The samples were then extracted using vortex oscillation and centrifugation, discarding the n-hexane layer. Take 4 mL of the acetonitrile layer was purify with 400 mg of anhydrous magnesium sulfate and 300 mg PSA. The supernatant was evaporated to near dryness using liquid and subsequently re-dissolved in water for measurement. The separation was performed using ACQUITY UPLC HSS T3 (100 mm×2.1 mm, 1.8 µm) column, with a mobile phase of water-methanol, in electrospray ionization positive ion mode and multi-reaction monitoring mode.ResultsThe method demonstrated a strong linear relationship for acrylamide detection within the range of 1.0~100 ng/mL (R2>0.999 1), with detection and quantitation limits of 0.25 µg/kg and 0.82 µg/kg, respectively. Recovery tests at three different concentration levels in various sample matrices yielded an average recovery rate of 91.3%~97.6%, with RSD values ranging from 1.3%~4.6%. Analysis of 65 commercially available naan samples revealed acrylamide contents ranging from 17.4~207.5 µg/kg, with significant differences observed among different types of Naan (H=23.10, P<0.05).ConclusionThe proposed method features minimal sampling volume and reagent consumption, along with a rapid and straightforward process that yields accurate results. It is applicable to various types of naan products, demonstrating its versatility and efficiency.